SRM drive for electric vehicles with solar PV-powered and hysteresis current controller based minimization of torque ripple - Balasubramaniam, Karunamoorthy (AIP conference proceedings, 2024)
Electric vehicles (EVs) are extensive R&D subject as they provide viable solutions for reducing green house gas emissions. SRM (switch reluctance motors) were among the most promising motor drives for electric vehicle (EV) usage. Electric Vehicle's mileage can be extended by using solar panel in vehicle, the vehicle's dependence on the battery can be reduced. To regulate the flow of energy in between Photo Voltaic module, the battery, and the SRM based on the phase winding characteristics of the SRM, this paper proposes a tri port inverter. Torque ripples of Switched Reluctance Motor (SRM) reduced. To reduce the Torque ripples of the switch reluctance motor, an indirect torque control approach employing the torque sharing function (TSF) is used. Closed-loop velocity control can be achieved by proportional and integral control. An Hysteresis current controllers are implemented for the development of gate pulse to the converters. The result of the performance of Switched Reluctance Motors (SRMs) can be showed by Matlab / Simulink based simulation in the motor drive industry with minimal copper loss. Hysteresis Current Control Overcomes existing peak-to-peak current control methods and provides better reduction of Torque ripples.